If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 7) + -15 = -3 Reorder the terms: 4(7 + x) + -15 = -3 (7 * 4 + x * 4) + -15 = -3 (28 + 4x) + -15 = -3 Reorder the terms: 28 + -15 + 4x = -3 Combine like terms: 28 + -15 = 13 13 + 4x = -3 Solving 13 + 4x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 4x = -3 + -13 Combine like terms: 13 + -13 = 0 0 + 4x = -3 + -13 4x = -3 + -13 Combine like terms: -3 + -13 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| -3(x+6)-41=1-36 | | 5x-5=5x+45 | | -4(4u-8)+6u=6(u+5) | | 2x^2+24x+69=y | | -2n-4=8 | | z-16=-19 | | 12a+9b= | | 4-3(x+4)=-12 | | f(-4)=2x-2 | | 5x=8x-15x | | 3x+-4=2x+1 | | xy+x= | | 0.25(x+10)=125.00 | | -5(v+2)=5v-2+2(4v+3) | | -32.519-5.6b=3.9(1+7.1b)+.2 | | (x^2+196)/(x-196) | | 4+2(5u-3)=-2(6u-4)+6u | | 9x^7y^5+18x^5y^4+27xy=0 | | 0.8+0.7(0.04)= | | 3(22)+3(4)= | | 4x+9-6x=33 | | 12t2/5 | | (5/6-1/5)/2/3 | | -8=32+-5q | | 6x-8+2(5x+1)=-2(x+2) | | 1/8(9+j)=4 | | 5x^3+8x^2-19x+6=0 | | 15y^2-17yz-4z^2= | | 0.25/0.5 | | 5/7+7m/3=71/21 | | 2(4z-1)-4(z-5)= | | -2+5/6+7/9 |